STRENGTH ANALYSIS OF SCRAPER BUCKET BASED ON THE COUPLING OF HYPERMESH- EDEM-PATRAN - LI JianGuo; SHI BoQiang; LIU RuiYue; ZHANG Hao (Jixie qiangdu)
Bucket force is simplified as concentrated force or uniform force in traditional bucket strength analysis,which will result in inaccurate bucket strength analysis result. Taking Sandvik 1400 e scraper as an example in this paper,carrying out pretreatment on the bucket based on Hyper Mesh,simulating scraper working process by EDEM,it is obtained that bucket is characterized by complication and variable load during scraper operation. By way of coupling discrete element and finite element,bucket was loaded precisely,then bucket strength analysis and wear calculation were completed,which will provide theoretical basis for bucket structure optimization.